ENVIRONMENTAL ACCOUNTING: EXTERNALITY PLANNING MODEL FOR PALU SPECIAL ECONOMIC AREA (SEZ) - Mustamin, Mustamin; Andi Mattulada; Maskuri Sutomo; Ikbal B; Abdul Kahar; Muhammad Nasir; Ikbal Abdulla (Bajang Institute, 2023)
The sustainability of the externalities of the Palu Special Economic Zone (KEK) provides legitimacy for managers, especially negative externalities, such as economic, social, environmental, legal and governance dimensions. Social dialogue really needs to be carried out to produce social license. As a result, the social license that has been obtained will become an important note as a reference and evaluation in assessing the performance of companies operating in the regional area. The role of environmental accounting for the sustainability of the externalities of the Palu Barus Special Economic Zone (KEK) focuses on processes that exert control over the impact of the company's production activities so that various negative externalities can be handled or minimized. Therefore, Estate managers must realize that they must increase profitability and take care of everything related to their survival in society directly or indirectly. This awareness produces a solution to the concept of sustainable development. Therefore, the managers of the Palu Special Economic Zone (KEK) and company owners operating within the area ensure that every decision is directed towards sustainability. Management accounting and control play a major role in creating information and therefore need to be considered as society seeks a transition to sustainability. Environmental accounting also plays an important role in trying to identify externalities, such as determining what is the subject of the account (the company's production activities, products produced by all companies operating within and outside the regional area, determining which externalities will be identified. The potential for negative externalities to occur if there is dialogue social services are not implemente